TINJAUAN HUKUM PROGRAM NASIONAL AGRARIA DI KABUPATEN SUKOHARJO - Samadi, Wibowo Murti; Suryanto, Edy - (Wacana Hukum, 2012)
Abstract: BPN is an institution that is authorized to perform the duties of government land,among others implement acceleration land registration. Based on GovernmentRegulation No. 24/1997 concerning PRONA (national programe) policies, namelyproviding land registration services and legal certainty as to realize the achievement ofchess orderly land sector. If Government Regulation No. 24/1997 implemented properly,it will provide legal certainty, that the rule of law: land rights holders; lay of the land;acreage and others. Completeness and actual information on every subject in the landregistration law, it will be easier to take legal actions against the parcel of land that hasbeen registered.Key words: national programe, acceleration of land registration.